1998
DOI: 10.2105/ajph.88.7.1105
|View full text |Cite
|
Sign up to set email alerts
|

Public health nihilism vs pragmatism: history, politics, and the control of tuberculosis.

Abstract: Tuberculosis (TB) began to decline in the Western world in the mid- to late 1800s. In the United States, the disease receded until the mid-1980s, when that trend was reversed. Although the TB epidemic in the United States subsided in response to public health interventions, it sparked a controversy regarding the relative value of targeted public health measures vs broad social reform. That controversy, which echoed earlier debates calling for structural reform over public health programs, was further strengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 23 publications
0
52
0
2
Order By: Relevance
“…Ironically, in the first half of the last century, farmers, consumers and legislators repeatedly resisted attempts to make testing of cattle and, more importantly, pasteurisation of milk compulsory in Britain, despite overwhelming evidence (particularly from the USA [43]) of its positive impact on public health.…”
Section: Discussionmentioning
confidence: 99%
“…Ironically, in the first half of the last century, farmers, consumers and legislators repeatedly resisted attempts to make testing of cattle and, more importantly, pasteurisation of milk compulsory in Britain, despite overwhelming evidence (particularly from the USA [43]) of its positive impact on public health.…”
Section: Discussionmentioning
confidence: 99%
“…The historical trend of TB mortality decline Several authors (McKeown, 1976;Szreter, 1988;Fairchild & Oppenheimer, 1998) have reported and investigated the decline in mortality due to TB over time. These studies mainly used data from England and Wales during the 19th and early 20th centuries in order to make interpretations about the reasons why TB mortality declined over time.…”
Section: Killing Germs Versus Improving Immunity: What Can Eradicate mentioning
confidence: 99%
“…78 Due to financial reasons, many sanatoriums released patients before they were completely healthy. 79 The Public Affairs Committee of the U.S. Chamber of Commerce estimated that in the early years of sanatoriums, a third of the patients left while they were still sick. 80 The outside world was well aware that some of the ex-sanatorium patients were not fully healed; as a result, many people viewed ex-patients as contagious.…”
Section: Middle Agesmentioning
confidence: 99%